Issues of electronic banking services: The case of commercial bank of Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The banking sector has made significant investments in the use of information technology during the last 20 years. Most banks have relied on electronic work to complete transactions and provide banking services, and they have become effective competitive means in digital and knowledge-based economies. Technological innovations have played an important role in the banking industry by creating value for banks and financial institutions, enabling them to expand the range of their products and services beyond the constraints of time and space, and contributing to enhancing their competitiveness more effectively. However, electronic banking brings along various issues and risks that require identification and management. This paper aims to clarify the difficulties the online banking sector is facing as well as the main complaints from Customers. Using a questionnaire to get specific data about the main issues of electronic banking services with a focus on the customer perspective. The findings revealed that there is a lack of knowledge and awareness of the e-banking system among the Iraqi bank's customers. Due to insufficient knowledge and a lack of confidence in e-banking services, some customers have not yet embraced internet banking. The research reached a number of recommendations, the most important of which is the necessity of providing the necessary infrastructure to implement electronic banking, and working to familiarize bank customers with the importance of modern technology and benefiting from electronic banking services.